2020
DOI: 10.2174/1745017902016010017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Mental Health Status Among Pre-Hospital Healthcare Staff

Abstract: Introduction:Mental stress amongst pre-hospital Emergency Medical Services (EMS) workers is an iceberg phenomenon; owing to unique occupational stressors faced by them. This study was aimed to examine the mental health status of pre-hospital EMS workers and its correlation with Post-Traumatic Stress Disorder (PTSD) and Work Environment Scale (WES). Methods:This cross-sectional study incorporated 224 emergency EMS members from urban and road EMS bases in eastern Iran in 2018. General Health Questionnaire (GHQ-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…By services, there have been differences of more than one point in the GHQ-12 among nurses working in PC = 2.94 (SD = 3.41), as compared to those working in emergency services 4.17 (SD = 3.79). This could be seen in the study by Abbaspour et al ( 43 ), where 39.7% of health professionals working as OHES in Iran had high levels of risk for mental health impairment. This phenomenon can be explained by the care overload to which EC nurses are exposed.…”
Section: Discussionmentioning
confidence: 84%
“…By services, there have been differences of more than one point in the GHQ-12 among nurses working in PC = 2.94 (SD = 3.41), as compared to those working in emergency services 4.17 (SD = 3.79). This could be seen in the study by Abbaspour et al ( 43 ), where 39.7% of health professionals working as OHES in Iran had high levels of risk for mental health impairment. This phenomenon can be explained by the care overload to which EC nurses are exposed.…”
Section: Discussionmentioning
confidence: 84%
“…Patients with chronic kidney failure, in addition to numerous physiological changes, face many psychological stresses. [ 5 ] On the one hand, due to the awareness of the deterioration of their disease, these patients are forced to bear the stress of grueling treatment measures, including dialysis, and however, with the prolongation of the disease, their psychosocial functioning is severely affected,[ 6 ] and most patients do not adapt to problems and tensions and suffer behavioral changes such as anxiety, depression, and isolation. [ 7 ] Studies have shown that rapid diagnosis and treatment of anxiety, depression, and stress increase the quality of life of patients undergoing hemodialysis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…7 These symptoms can also affect people's mental health, even leading to mental disorders such as PTSD. 8 A cross-section study on family members of staff in five hospitals in China during the outbreak of COVID-19 involving 822 people reported the prevalence of anxiety and depressive symptoms as 33.73% and 29.35%, respectively. 9 Depression is a common negative emotion experienced by individuals and medical staff during an infectious disease outbreak.…”
Section: Introductionmentioning
confidence: 99%